Peninsular India in Gondwana: The Tectonothermal Evolution of the Southern Granulite Terrain and its Gondwanan Counterparts - Collins, A.; Clark, Christopher; Plavsa, Diana (Elsevier Science BV, 2014)
Peninsular India forms a keystone in Gondwana, linking the East African and Malagasy orogens with Ediacaran–Cambrian orogenic belts in Sri Lanka and the Lützow Holm Bay region of Antarctica with similar aged belts in Mozambique, Malawi and Zambia. Ediacaran–Cambrian metamorphism and deformation in the Southern Granulite Terrane (SGT) reflect the past tectonic setting of this region as the leading vertex of Neoproterozoic India as it collided with Azania, the Congo–Tanzania–Bangweulu Block and Kalahari on one side and the Australia/Mawson continent on the other. The high-grade terranes of southern India are made up of four main tectonic units; from north to south these are a) the Salem Block, b) the Madurai Block, c) the Trivandrum Block, and d) the Nagercoil Block. The Salem Block is essentially the metamorphosed Dharwar craton and is bound to the south by the Palghat-Cauvery shear system — here interpreted as a terrane boundary and the Mozambique Ocean suture. The Madurai Block is interpreted as a continuation of the Antananarivo Block (and overlying Palaeoproterozoic sedimentary sequence — the Itremo Group) of Madagascar and a part of the Neoproterozoic microcontinent Azania. The boundary between this and the Trivandrum Block is the Achankovil Zone, that here is not interpreted as a terrane boundary, but may represent an Ediacaran rift zone reactivated in latest Ediacaran–Cambrian times.